Analyzing the Educational Attainment of People in Nepal from Gender Perspective - Karki, Rita Devi; Karki, Tek Mani (Education and Development, 2020)
Education is a key tool for human civilization but many people are deprived of it and do not have equal chance to achieve it from gender point of view in society, though everyone has an equal right to get it. In this context, this study tries to explore the literacy status, educational attainment. The major concern of preparing this article was to study this issue extracting the data from two immediate past censuses of Nepal and analysing them by using the Microsoft Excel programme. Humanities and Arts, Business and Administration, Education, Science, and Social and Behavioural Science are supposed to be more selected subjects of study for both males and females at the national level. More gender gap in terms of literacy and level of education seems to occur though the level of education increases in all provinces.